The cosmic ray all-particles spectrum from the NUCLEON experiment in comparison with ground-based experiments data. Issue 9 (1st November 2022) - Turundaevskiy, A.; Karmanov, D.; Kovalev, I.; Kudryashov, I.; Kurganov, A.; Panov, A.; Podorozhny, D.
Abstract: The cosmic ray all-particles spectrum is a very important result obtained by the NUCLEON space experiment. This spectrum was directly measured up to energies near 500 TeV. The ground-based experiments provide very large statistics but their results depend on applied models. The NUCLEON experiment allows comparison with results of direct measurements and data of ground-based experiments. The all-particles spectrum is presented. The shape of this spectrum differs from the power-law dependence. We show in this paper that this feature is caused by a pre-knee softening found in the rigidity spectra measured by the NUCLEON experiment. The all-particles spectrum is close to the data from ground-based experiments HAWC and TAIGA.